Hybrid Beamforming for millimetre Wave massive MIMO Communication: A Survey - Rajpreet Singh, Paras Chawla (International Journal of Advanced Science and Technology, 2020)
Hybrid Beamforming Massive MIMO Systems for millimetre Waves are seen as fundamental technologies to meet continuously increasing demand of data traffic in near future with seamless connectivity and service quality. For millimetre waves communication the conventional fully digital beamforming techniques become impractical as they demand for high power, cost and complexity. The hybrid beamforming architecture minimizes the hardware cost, complexity, power consumption with nearly optimal performance which is the need of future generation equipment’s. Therefore, hybrid beamforming received significant attention form research community specifically for 5th generation wireless networks. This paper provides insights offundamental keypoints, hybrid beamforming structure, associated challenges anddetailed survey ofprominent research work with respect to analog beamforming metrics, digital beamforming metrics and spectral efficiency as performance parameter.